PANCHKARMA MANAGEMENT OF SPASTIC DIPLEGIC CEREBRAL PALSY IN CHILDREN: A SINGLE CASE STUDY - Meena, *Aanchal; Kumar Sharma, Mahesh; Prakash Sharma, Gyan; Swami, Preeti (International Journal of Ayurveda and Pharma Research, 2019)
Cerebral Palsy is a neurological disorder that affects a child’s movement, motor skill and muscle tone. The present case is of a patient having Spastic diplegic Cerebral Palsy which was successfully managed with Panchakarma treatment. A four year old boy complaint of global developmental delay with predominantly gross developmental delay, can’t feed himself, unable to sit without support, does not roll over, has age appropriate non-verbal communication was treated with Panchakarma procedures. The Ayurvedic diagnosis of the case was Shiro-Marmabhighatajsankochajanyavatavyadhi. We have formulated an Panchakarma therapy protocol to improve the condition of spastic diplegic CP patients. Result was observed in the form of GMFCS Level and significant changes in investigations.